Radiotherapy in the Era of Immunotherapy With a Focus on Non-Small-Cell Lung Cancer: Time to Revisit Ancient Dogmas? - Khalifa, Jonathan; Mazieres, Julien; Gomez-Roca, Carlos; Ayyoub, Maha; Moyal, Elizabeth Cohen-Jonathan (Frontiers in Oncology, 2021)
Radiation-induced immune effects have been extensively deciphered over the last few years, leading to the concept of a dual immune effect of radiotherapy with both immunostimulatory and immunosuppressive effects. This explains why radiotherapy alone is not able to drive a strong anti-tumor immune response in most cases, and this underlies the rationale for combining both radiotherapy and immunotherapy. This association has generated a considerable interest in this field, and hundreds of trials are currently ongoing assessing such an association in oncology. However, while some trials have provided unprecedented results or promises, many hopes have been disappointed, underlying that many questions remain as how to optimize the combination of both treatment modalities. This narrative review aims at revisiting old and well-established concepts of radiotherapy relating to dose, fractionation, target volumes or organs at risk, in the era of immunotherapy, in order to propose potential innovative approaches to be further assessed when considering a radio-immunotherapy association, especially in the field of non-small cell lung cancer (NSCLC). We finally propose a framework to optimize the association, with pragmatic approaches depending on the stage of the disease.